(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Background: Background: Mechanical ventilation is a form of life support technology used to perform the work of breathing for children who are unable to do this on their own .Thus providing adequate nursing care for children on mechanical ventilation is the most contribution to the successful management and outcomes. Aim : To evalute the expected outcomes of nursing care provided to children on mechanical ventilation. A descriptive study was conducted on 60 nurses and 30 children on mechanical ventilation in paediatric intensive care unit at Al -Ahrar Educational Zagazig Hospital, General Zagazig hospital and Zagazig University Hospital. Tools: Structured questionnaire interview , observational checklist and children assessment sheet were used to evaluate nursing care provided to children on mechanical ventilation. Results : Revealed that two thirds of studied nurses had poor knowledge and less than two thirds had insufficient practice about nursing care provided for children on mechanical ventilation as well as nurses' qualification and years of experience in a PICU had high positive effect on total practice Conclusion: studied nurses had poor knowledge and insufficient practice about nursing care provided for children on mechanical ventilation. Therefore the expected outcomes of nursing care provided to children on mechanical ventilation were unsatisfactory. Recommendation: Based on the results of the present study in –service training programs should be developed for nurses directed toward all aspects of care provided for children on mechanical ventilation.